599 Circulating tumour cells in breast and ovarian cancer: size-based isolation and ex vivo expansion. (14th December 2020) - Mohamed, Bashir; Ward, Mark; Bates, Mark; Spillane, Cathy; Kelly, Tanya; Martin, Cara; Gallagher, Michael; Kennedy, John; Saadeh, Fears Abu; Gleeson, Noreen; Brooks, Doug A; Brooks, Robert D; et al.
Abstract : Introduction/Background: Circulating tumour cells (CTCs) play a crucial role in cancer dissemination and cellular extravasation leading to metastasis. There are only a limited number of CTCs per clinically/ethically allowed cancer patient`s blood draw and expanding this population of cells in vitro is crucial in order to provide a reliable number of cells to analyse CTC biology. CTCs can grow in a hypoxic environment and the activation of hypoxia-inducible factor (HIF-1α) results in increased cell survival and cellular proliferation, leading to cancer progression. Our aim was to optimise cell culture conditions using cobalt chloride (CoCl2) as a chemical inducer of hypoxia that would allow us to examine growth of cells in real time. Primary ovarian cancer cells would be used for the hypoxia optimisation and conditions adapted ovarian/breast CTC cultures in vitro. Methodology: Primary ovarian cancer cells were cultured in modified media supplemented with various concentrations of CoCl2 for HIF1 α induction (50, 100, 150 and 200 uM). Cell viability and the expression of HIF-1α, PHH3, EpCAM and HER2 were examined in these cells using either ELISA, Immunoblotting or Immunofluorescence techniques. CTCs were isolated from breast and ovarian cancer patients using the ScreenCell® Cyto R device and cultured in specially modified media optimised for CTC culture supplemented with 20% FCS, growth factors and additives including: FGF-2, FGF-10, Nicotinamide, Y-27632, Primocin and CoCl2. EpCAM and HER2 were examined in cultured and expanded CTCs using Immunofluorescence techniques. Results: HIF-1α expression was induced and cell proliferation and viability were maintained in the primary ovarian cancer cells at a concentration of 100 µM of CoCl2. Subsequently this concentration was used for the culturing of isolated CTCs. Using this condition, CTCs were successfully cultured and expanded for more than nine weeks. Based on the morphological and phenotypical characterisation, two phenotypes of CTCs were isolated from a breast cancer patient; epithelial-like expressed EpCAM and quasi-mesenchymal express HER2. Conclusion: We demonstrated the feasibility of culturing cancer patient blood derived CTCs under hypoxic conditions. We also demonstrated the presence of heterogenous CTC populations; classical epithelial-like CTCs and quasi-mesenchymal subtypes in a breast cancer patient and their corresponding molecular phenotypes. Our work also demonstrated the suitability of size-based isolation for this culturing approach. Disclosures: The authors have no conflict of interest. Disclosures: The authors have no disclosures relevant to this work Funders: British Gynaecological Cancer Society, Ovarian Cancer Action, Target Ovarian Cancer. References: https://www.nice.org.uk/guidance/cg122 (accessed 13th November 2020) Kumar S, Long J, Rudge G, Manchanda R, Fotopoulou C, Wood N, Duncan T, Balega J, Mukhopadhyay A, Broadhead T. Socqer-2 study: Preliminary analysis of multicentre recruitment after surgery in advanced ovarian cancer. In International Gynaecologic Cancer Society 2016. Lisbon, Portugal. Hall M, Savvatis K, Nixon K, Kyrgiou M, Hariharan K, Padwick M, Owens O, Cunnea P, Campbell J, Farthing A, Stumpfle R, Vazquez I, Watson N, Krell J, Gabra H, Rustin G, Fotopoulou C. Maximal-effort cytoreductive surgery for ovarian cancer patients with a high tumor burden: Variations in practice and impact on outcome. Ann Surg Oncol 2019;26 (9):2943–2951. Timmermans M, Sonke GS, Slangen BFM, Baalbergen A, Bekkers RLM, Fons G, Gerestein CG, Kruse AJ, Roes EM, Zusterzeel PLM, Van de Vijver KK, Kruitwagen R, van der Aa MA. Outcome of surgery in advanced ovarian cancer varies between geographical regions; opportunities for improvement in the netherlands. European journal of surgical oncology : The journal of the European Society of Surgical Oncology and the British Association of Surgical Oncology 2019;45(8): 1425–1431 Warren JL, Harlan LC, Trimble EL, Stevens J, Grimes M, Cronin KA. Trends in the receipt of guideline care and survival for women with ovarian cancer: A population-based study. Gynecologic oncology 2017;145 (3):486–492 Katherine E Henson, Lucy Elliss-Brookes, Victoria H Coupland, Elsita Payne, Sally Vernon, Brian Rous, and Jem Rashbass. Int J Epidemiol 2020 Feb; 49(1): 16–16h. Published online 2019 Apr 23. doi: 10.1093/ije/dyz076